Amalgamation of rare-earth neodymium ions with ZnO nanoparticles: extensive investigations into the microstructure and optical properties. (1st January 2023) - Senthil Kumari, S; Nirmala, W; Chidhambaram, N; Prabu, M; Gobalakrishnan, S; Thirumurugan, Arun
Abstract: A comprehensive study is envisioned to examine the influence of rare-earth (RE) metal doping on the zinc oxide (ZnO) matrix. A wet-chemical methodology is adopted to synthesize pristine and neodymium (Nd)-doped ZnO nanoparticles (NPs). Crystal structure analysis substantiates that RE doping does not form any secondary phases related to RE metal clusters or oxides. The average crystallite and apparent strain values of the synthesized NPs are obtained from the size-strain plot approach. In addition to the typical absorption edge of ZnO, the characteristic absorption bands of Nd 3+ ions are also detected in the doped ZnO NPs. Light-emission studies reveal photoluminescence quenching for up to 3 wt.% of Nd-doping, and 5% doping causes an enhanced ultraviolet emission in the Nd-doped ZnO matrix. Additional functional groups that co-exist with the NPs are identified using Fourier transform infrared spectroscopy. Energy dispersive x-ray studies corroborate the existence of constituent elements in the doped ZnO matrix.